Demographic responses to climate‐driven variation in habitat quality across the annual cycle of a migratory bird species. Issue 6 (11th June 2022) - Saracco, James F.; Cormier, Renée L.; Humple, Diana L.; Stock, Sarah; Taylor, Ron; Siegel, Rodney B.
Abstract: The demography and dynamics of migratory bird populations depend on patterns of movement and habitat quality across the annual cycle. We leveraged archival GPS‐tagging data, climate data, remote‐sensed vegetation data, and bird‐banding data to better understand the dynamics of black‐headed grosbeak ( Pheucticus melanocephalus ) populations in two breeding regions, the coast and Central Valley of California (Coastal California) and the Sierra Nevada mountain range (Sierra Nevada), over 28 years (1992–2019). Drought conditions across the annual cycle and rainfall timing on the molting grounds influenced seasonal habitat characteristics, including vegetation greenness and phenology (maturity dates). We developed a novel integrated population model with population state informed by adult capture data, recruitment rates informed by age‐specific capture data and climate covariates, and survival rates informed by adult capture–mark–recapture data and climate covariates. Population size was relatively variable among years for Coastal California, where numbers of recruits and survivors were positively correlated, and years of population increase were largely driven by recruitment. In the Sierra Nevada, population size was more consistent and showed stronger evidence of population regulation (numbers of recruits and survivors negatively correlated). Neither region showed evidence of long‐term population trend. We found only weak support for most climate–demographic rate relationships. However, recruitment rates for the Coastal California region were higher when rainfall was relatively early on the molting grounds and when wintering grounds were relatively cool and wet. We suggest that our approach of integrating movement, climate, and demographic data within a novel modeling framework can provide a useful method for better understanding the dynamics of broadly distributed migratory species. Abstract : GPS‐tagging data show distinct molting and wintering regions for populations of a migratory bird species black‐headed grosbeak ( Pheucticus melanocephalus ) that breed in California, USA. Drought conditions across the annual cycle and rainfall timing during the molting period are reflected in annual variation in habitat characteristics. Integrated population models that incorporate climate covariates from distinct periods of the annual cycle as drivers of demographic rates can inform variation and trends of populations at regional scales.